PENGEMBANGAN PERANGKAT PEMBELAJARAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) PADA MATERI KELARUTAN DAN HASIL KALI KELARUTAN (Ksp) UNTUK MENINGKATKAN HASIL BELAJAR KIMIA SISWA SMA KELAS XI IPA - Natalia Peni (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2018)
This study aims to produce chemistry learning materials of cooperative learning model TAI type that is improve to increase chemistry learning achievement of high school students at grade XI. Development of learning materials used 4-D model and tested in grade XI SMAKFrateran Surabaya second semester academic year 2015/2016 with one -group pretest-posttest design. Collecting data used observation, validation, questionnaires and tests. The data were analyzed through quantitative descriptive. The results showed that learning materials that was developed in valid and reliable category. The percentage of lesson plan feasibility beetween 98,41% - 99,49% in good category. The student learning achievement in knowleage and practical skills compentence reached completeness, whereas attitudes compentence growing during learning process. Students’ learning achievement in knowleage compentence analyzed with N-gain. The increase of N-gain in high category. Student gave positive / high response on learning that implemented by teacher. Grounded on the result date can it concluded that chemistry learning materials of cooperative learning model TAI type that is unsuitable to increase chemistry learning achievement.